TINDAK TUTUR DIREKTIF DALAM NOVEL KITAB CINTA YUSUF ZULAIKHA KARYA TAUFIQURRAHMAN AL-AZIZY - Mahmuda, Rifaatul; Salem, Laurensius; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is Directive Speech Acts in the Novel Cinta Yusuf Zulaikha by Taufiqurrahman Al - Azizy. The problem in this study is What is the form of the requestive directive speech,directive quentions,requirement’s directive say,directive speech acts of prohibitive,permissive directive speech acts and directive speech acts of advisories in the Novel Cinta Yusuf Zulaikha? The purpose of this study is Describing the form of the requestive directive speech acts,directive quentions,directive speech acts,directive prohibitive speech acts,directive speech acts permissive,directive advisories in Yusuf Zulaikha’s Book of Love? The research method used is a descriptive research method, with the form of research being qualitative. Subject of Research: Novel Cinta Yusuf Zulaikha by Taufiqurrahman Al - Azizy.Data collection techniques in this study used a Documentary Study, while the data collection tools used were researchers as a key instrument Data analysis techniques used descriptive qualitative techniques. Based on the results of the research data processing, it can be concluded that The directive requestives’ The most dominant act of speech requestives used is asking, which consists of eighteen discourses. quentions of speech act, The author uses the most questions asked consisting of forty-five discourses. requirements The author uses a lot of requirements that consist of three discourses. prohibitives The author presents a bit of forbidding discourse consisting of only two contexts. permissives’ speech acts, The most common discourse used is the context of agreeing sentences.advisiories. The most widely used context is the sentence suggested.Suggestion Researchers hope that the results of this study can be used as inspiration for language or literary researchers.Keywords: Pragmatics, Imperatives, Outdoor Media